Revitalisasi Desa Mekarjadi: Optimalisasi Potensi Lokal melalui Pendekatan Partisipatif dalam Kuliah Kerja Nyata - Teguh Ikhlas Ramadhan; Sigit Wahyu Nugraha; Alisa Nur Pratiwi (Universitas Perjuangan Tasikmalaya, 2026)
This community service program implemented a participatory approach through the Participatory Development Real Work Lecture (KKN-PM) to revitalize the potential of Mekarjadi Village, Ciamis Regency. The comprehensive assessment revealed several critical challenges, including limited digital marketing capabilities among MSMEs, suboptimal post-harvest agricultural product management, inadequate disaster preparedness, and traditional administrative systems. The methodology employed participatory rural appraisal techniques, including direct observation, focused group discussions, and collaborative planning with village stakeholders. Implementation strategies encompassed digital literacy training for MSMEs, sustainable agricultural practices using environmentally friendly pest control, participatory disaster risk mapping, development of village profile websites, and school literacy movements. The results demonstrated significant achievements: 75% of MSME participants successfully adopted digital marketing tools, comprehensive disaster risk maps were established across three hamlets, a functional village website was launched, and student literacy engagement increased by 80%. The program successfully enhanced community capacity in local resource management, although longitudinal mentoring remains essential for sustainable impact. The participatory methodology proved highly effective in ensuring community ownership and designing contextually appropriate interventions that addressed genuine local needs while fostering sustainable development principles.